Modular Approach to Implement Model Predictive Control on Three Phase Voltage Source Inverter - Muhammad Abbas Abbasi; Abdul Rashid Bin Husain; Hasan Alqaraghuli (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
A modular abstraction is presented to implement model predictive control (MPC) on a three phase two level voltage source inverter to control its output current. Traditional ways of coded implementation do not provide insights into the complex nature of MPC; hence a more intuitive, logical and flexible approach for hardware implementation is conceptualized in the form of signal flow graphs (SFGs) for estimation, prediction and optimization. Simulation results show good performance of the approach and easier code generation for real time implementation. RL load is assumed for the inverter and the importance of choosing load inductance and sampling time ratio is emphasized for better control performance.